2017
DOI: 10.3892/etm.2017.5679
|View full text |Cite
|
Sign up to set email alerts
|

Target therapy of TRIM-14 inhibits osteosarcoma aggressiveness through the nuclear factor-κB signaling pathway

Abstract: Osteosarcoma is the most common cause of cancer-associated mortality and the prognosis is yet to be fully elucidated due to the paucity of effective therapeutic targets that significantly influence the quality of life and mean survival rates of patients with osteosarcoma. Studies have showed that tripartite motif-containing (TRIM)-14 is a member of the TRIM protein family that has a vital role in tumor progression and metastasis and promotes angiogenesis, invasion and apoptotic resistance of bone cancer. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…In recent years, many studies have shown that TRIM family proteins such as TRIM2 19 , TRIM21 8 , TRIM14 16 , TRIM44 20 , TRIM59 21 , and TRIM66 22 are known to be dysregulated and involved in the pathogenesis of OS. However, the biologic functions of most TRIM proteins in OS, including TRIM46, have not been well elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, many studies have shown that TRIM family proteins such as TRIM2 19 , TRIM21 8 , TRIM14 16 , TRIM44 20 , TRIM59 21 , and TRIM66 22 are known to be dysregulated and involved in the pathogenesis of OS. However, the biologic functions of most TRIM proteins in OS, including TRIM46, have not been well elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…TRIM21 activates the NF-κB signaling pathway by inducing IKKβ ubiquitination 15 and increases the proliferation and chemoresistance of OS cells 8 . TRIM14 downregulation results in the inhibition of OS cell growth and promotes their apoptosis through NF-κB signaling pathway 16 . Furthermore, TRIM23 regulates PPARγ protein stability through atypical ubiquitin conjugation to PPARγ 17 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, IKBKB [28,29] has been shown to take part in tumor growth via NF-κB activation and the phosphorylation-dependent inhibition of tumor suppressors. A previous study [30] indicated that the protein expression levels of IKBKB were remarkably decreased in U-2OS cells after treated with Chanti-TRIM, while TRIM induced the expression levels of p65, IKKβ and IκBα. The above finding suggested that Chanti-TRIM may impede the aggressive phenotypes via the MMP-9-induced NF-κB signaling pathway in vitro.…”
Section: Introductionmentioning
confidence: 90%
“…In addition, TRIM46 acts as an oncogene in OS by interacting with and ubiquitinating PPARα (peroxisome proliferator-activated receptor α), leading to the activation of the NF-κB signaling pathway [ 251 ]. Activation of the NF-κB pathway is also positively correlated with TRIM52 [ 252 ], TRIM14 [ 253 ], and TRIM31 [ 254 ] and promotes cancer development in cancers. In NSCLC, TRIM13 behaves as a tumor suppressor through by negatively regulating the NF-κB pathway [ 255 ].…”
Section: The Trim Family and Cancer Pathologymentioning
confidence: 99%